2015
DOI: 10.1021/acs.jafc.5b00509
|View full text |Cite
|
Sign up to set email alerts
|

Carotene Reactivity in Pink Grapefruit Juice Elucidated from Model Systems and Multiresponse Modeling

Abstract: This study was carried out to assess the impact of pink grapefruit juice composition and structure on the degradation kinetics of lycopene and β-carotene using model systems and multiresponse modeling. Carotenes were heated at four temperatures in their native matrix (juice) or were extracted and incorporated in water/ethanol emulsion systems formulated with or without ascorbic acid or naringin. Kinetic analysis showed that the rate constants and activation energy were lower for lycopene than for β-carotene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The main degradation products identified are cis ‐isomers, mainly 13‐ cis ‐ and 9‐ cis ‐β‐carotene (Achir et al . ). Several studies have reported the effect of cooking on the carotenoid contents of vegetables.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main degradation products identified are cis ‐isomers, mainly 13‐ cis ‐ and 9‐ cis ‐β‐carotene (Achir et al . ). Several studies have reported the effect of cooking on the carotenoid contents of vegetables.…”
Section: Resultsmentioning
confidence: 97%
“…b-carotene is subjected to isomerization and oxidation, followed by cleavage because of its unsaturated structure, particularly under the influence of heat and light during processing or storage. The main degradation products identified are cis-isomers, mainly 13-cis-and 9-cis-b-carotene (Achir et al 2015). Several studies have reported the effect of cooking on the carotenoid contents of vegetables.…”
Section: Antioxidant Contentsmentioning
confidence: 99%
“…Besides the antioxidant advantages of preserving all carotenoids, in future studies these encouraging results could be accompanied by sensory analyses to study organoleptic improvements in orange juice with ohmic pasteurization. (2013) and Achir , et al, (2015). them -particularly orange and grapefruit-is notably due to their high content in organoleptic and nutritional compounds of interest and among them carotenoids.…”
Section: Resultsmentioning
confidence: 99%
“…2 (Achir , Hadjal , Madani, Dornier, & Dhuique-Mayer, 2015;Hadjal, Dhuique-Mayer, Madani, Dornier, & Achir, 2013). These constants were calculated from the Confidence intervals of the simulated concentrations (eq.…”
Section: Kinetic Modellingmentioning
confidence: 99%
“…Carotenoids have been extensively studied in several model systems and plant matrices, revealing different factors affecting their stability, such as carotenoid type and physical form, oxygen concentration, presence of metals, exposure to light, severity of heat treatment, food matrix, and storage temperature [8][9][10][11][12][13][14]. In contrast, studies describing the chemical stability of carotenoid-rich colouring concentrates in food applications are rather limited, although this information would be industrially relevant for predicting carotenoid losses and colour changes in coloured food products throughout their shelf-life.…”
Section: Introductionmentioning
confidence: 99%